2022
DOI: 10.1371/journal.pone.0272018
|View full text |Cite
|
Sign up to set email alerts
|

Does intangible assets affect the financial performance and policy of commercial banks’ in the emerging market?

Abstract: In a digital and knowledge based economy, intangible assets are predominant and their role along with age and knowledge has become key success factors for firms. However, a very little attention was given to the intangible assets in the banking sectors’ in Ethiopia and the effect still not studied yet. Therefore, the aim of this study is to empirically examine the effect of intangible assets on the financial performance and policy of 17 commercial banks in Ethiopia from the year 2017 to 2020. Return on asset a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This is because this positive result is not statistically significant. When the literature is examined, Abebe Zelalem and Ali Abebe (2022), who conducted a study on the banking sector, obtained a positive result similar to the one in this study. Similarly, Awa Felix, Okwo, M. and Obinabo, C. (2020) investigated the impact of intangible assets of commercial banks on performance with random effects and found that goodwill and computer software have a positive and significant effect on return on assets.…”
Section: Conclusion and Recommendationssupporting
confidence: 77%
“…This is because this positive result is not statistically significant. When the literature is examined, Abebe Zelalem and Ali Abebe (2022), who conducted a study on the banking sector, obtained a positive result similar to the one in this study. Similarly, Awa Felix, Okwo, M. and Obinabo, C. (2020) investigated the impact of intangible assets of commercial banks on performance with random effects and found that goodwill and computer software have a positive and significant effect on return on assets.…”
Section: Conclusion and Recommendationssupporting
confidence: 77%
“…Highly liquid corporations should use money created internally that do not include the fixed payment of interest [65][66][67]. A positive association between liquidity and financial policy was also discovered by [62]. Thus, based on tradeoff theory and empirical arguments this study developed the hypothesis as;…”
Section: Liquiditymentioning
confidence: 95%
“…[ 61 ] Found a correlation between firm size and debt ratio in Malaysia. Additionally, [ 62 ] discovered that asset size has a significant impact on the monetary policy of commercial banks in the emerging market. Therefore, based on the above empirical arguments this study developed the hypothesis as;…”
Section: Literature Reviewmentioning
confidence: 99%